Job satisfaction of nurses at inpatients primary health care in Demak regency - Edy Soesanto; Arief Yanto; Ninin Irani; Satriya Pranata; Sri Rejeki; Priyo Sasmito (International Journal of Public Health Science (IJPHS), 2022)
The majority of activity among nurses in primary health care in Indonesia is still high for non-productive activities. Non-productive activities are closely related to job dissatisfaction then has an impact on work performance. This study aims to analyze the job satisfaction of nurses in primary health care facilities in Indonesia. This study used a quantitative descriptive design. The research used a cross-sectional approach. The subjects of this study are nurses (N= 226 people) who served in 15 inpatients' primary health care. The sampling technique uses a proportionate simple random sampling technique. Nurse job satisfaction instruments assess context factors and content factors. Nurse job satisfaction on context factor is in a good category by a big responsibility for nurse's work (55.2%), progress in work developed well (63.4%), nurses had the opportunity to achieve achievement (54.5%), nurses get great recognition for performance (58.6%) and feel their work is valuable (65.5%). Job satisfaction was supported by policy indicators, supervision, salary, interpersonal relationships, and good working conditions. On the other hand, nurses' job satisfaction on the content factor still needs to be optimized. This is supported by the job satisfaction of nurses on the indicators of responsibility, achievement, performance recognition that has not reached 60%. Therefore, job satisfaction among nurses in inpatient primary health care was quite good enough but still requires optimization on the content factor.